Efektifitas Layanan Bimbingan Kelompok dalam Mengurangi Kecemasan Berkomunikasi pada Siswa - Aswida, Wela; Marjohan, .; Syukur, Yarmis (Universitas Negeri Padang, 2012)
Abstract One purpose of Students to learn was to have good communication skills. In fact, some students have been anxiety in communicating. The research objective is to identify differences of student communications anxiety before and after group guidance service treatment. The research was using quantitative method that pre-experiment design. The discovering of student communications anxiety this research are: 1) before group guidance treatment was 76.76%. 2) after group guidance treatment was 49.78%. 3) there was a tendency that anxiety levels in communication after use group guidance was reduced.